Dwelling in New Delhi, dwelling in hybridity - Claudia Roselli (lo Squaderno, 2011)

(untitled)
I wake up in a ground floor bedroom of a fourth floor building. In the near dining room, the tv is kicking out loud Hindi voices, the musical refrain of a phone company ad. The family hosting me is a family of immigrants. The grandfather and the grandmother arrived in Delhi during the partition time. They originally grew up in Pakistan and met in the place where they live today, when the land was organized as a refugees camp. At the beginning, the refugees camp was only a wasteland. Then, with the passage of time, people started to build small pakka houses, a kind of self-built architecture made of simple oven-cooked red bricks, with a thatched roof.